2021
DOI: 10.1002/ppp.2123
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, morphometry, and ice content of ice‐wedge polygons in Tombstone Territorial Park, central Yukon, Canada

Abstract: Investigations of the regional distribution of ice‐wedge polygons and wedge‐ice volume allow for the assessment of the vulnerability of permafrost landscapes to thaw‐induced disturbances and related ecological feedbacks. Ice‐wedge polygons have been described in multiple studies in flat terrain and low‐gradient hillslopes, but few studies have examined ice‐wedge polygons in mountainous terrain. This study investigates the distribution, morphometry, and wedge‐ice content of ice‐wedge polygons in Tombstone Terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 50 publications
(98 reference statements)
1
19
1
Order By: Relevance
“…Our results appear to be consistent with these assumptions, but the nature of the substrate is often associated with landforms. 31,69 Our results also show some inconsistencies with the often expressed idea that hexagonal polygons are formed in fine, homogeneous deposits while orthogonal polygons are found in coarse and heterogeneous materials. 1,4,5,26,71 Further insight into the This study provides the first broad-scale empirical dataset describing the spatial distribution of TCCPs, ice-wedge polygons, and their characteristics over a large part of Nunavik.…”
Section: Relationship Between Network Geometry and Local Eco-geomorph...contrasting
confidence: 72%
See 4 more Smart Citations
“…Our results appear to be consistent with these assumptions, but the nature of the substrate is often associated with landforms. 31,69 Our results also show some inconsistencies with the often expressed idea that hexagonal polygons are formed in fine, homogeneous deposits while orthogonal polygons are found in coarse and heterogeneous materials. 1,4,5,26,71 Further insight into the This study provides the first broad-scale empirical dataset describing the spatial distribution of TCCPs, ice-wedge polygons, and their characteristics over a large part of Nunavik.…”
Section: Relationship Between Network Geometry and Local Eco-geomorph...contrasting
confidence: 72%
“…It has been suggested that grain size distribution of soil materials and networks and that thermal contraction coefficients may vary with different sediment deposits. 31,68,69 Thus, the stress field within certain substrates would not be homogeneous, such as in tills which are composed of various sediment sizes. 69 However, it can be deduced from our statistics that the shape and extent of the ground surface area exposed to cooling largely determine the 3D homogeneity (mainly orthogonal intersections) or heterogeneity (mainly hexagonal and random intersections) of the temperature gradients in the ground that induce the stress field responsible for thermal contraction cracking.…”
Section: Relationship Between Network Geometry and Local Eco-geomorph...mentioning
confidence: 99%
See 3 more Smart Citations